An HRM Framework for Manufacturing Companies of Bangladesh Mapping Employee Rights’ Protocols and Grievance Management System - Andalib, Tarnima Warda; Mohd Ridzuan, Darun (Informatics Publishing Limited, 2018)
Objective: This paper aims to propose an Human Resource Management (HRM) framework for the manufacturing companies of Bangladesh where Grievance Management System (GMS) and Employee Rights (ERS) protocols are mapped. Methods and Analysis: Researchers collected data of twelve listed manufacturing companies of Bangladesh where every company has customized HRM policies and practices dealing with employees. Bangladesh govt. has Bangladesh Labour Law for all the companies of Bangladesh, declared in the guideline named Bangladesh Labour Act 2006, where employees’ rights and related laws are clearly mentioned. Findings: Therefore, researchers developed a new HRM framework mapping new HRM components named ‘Employee rights’ and ‘Grievance management system’, which were always mentioned in separate guideline but never have been mapped in the framework before. Novelty / Improvement: Mapping the HRM framework with employees’ rights protocols and grievances management system motivates the employees by fulfilling their rights and by considering their wellbeing.